Zbiorowiska roślinne doliny Czerwonej Wody w Parku Narodowym Gór Stołowych - Pielech, Remigiusz; Dyderski, Marcin; Gazda, Anna; Hachułka, Mariusz; Horodecki, Paweł; Jagodziński, Andrzej; Kamczyc, Jacek; Kałucka, Izabela; Malicki, Marek; Skorupski, Maciej; Smoczyk, Michał; Wierzcholska, Sylwia (Leśne Prace Badawcze, 2018)
The Czerwona Woda River is the main watercourse in the Stołowe Mountains National Park and drains the major part of the Stołowe Mts. It was regulated in the past, but its channel has been spontaneously naturalized. Now, managed spruce forests grow along almost the entire length of this small mountain stream. The aims of the present study were to investigate diversity of plant communities connected with the Czerwona Woda stream and to prepare detailed vegetation maps. The results obtained can potentially be a reference for future restoration projects implemented in the Stołowe Mountains National Park. As a result of vegetation mapping, there were distinguished 20 plant communities representative of the current vegetation and 3 communities representative of the potential vegetation. Phytosociological data on the vegetation was documented by making 62 phytosociological relevés. Based on these, 9 forest communities were distinguished, of which 3 were classified into associations, 1 – into alliance, 5 – into secondary forest communities. Furthermore, there were distinguished 14 non-forest communities, of which 10 were classified into associations. Several of the phytosociological classes distinguished have been reported for the first time in the Stołowe Mountains National Park.